Ecological and Economic Consequences of Ignoring Jellyfish: A Plea for Increased Monitoring of Ecosystems. Issue 11 (4th November 2016) - Brodeur, Richard D.; Link, Jason S.; Smith, B. E.; Ford, M. D.; Kobayashi, D. R.; Jones, T. T.
Abstract : Gelatinous zooplankton can dominate the dynamics of marine ecosystems; can have major ecological, social, and economic impacts; are often indicative of broader ecosystem perturbations; and are increasingly being harvested by humans. Yet fisheries scientists typically do not monitor these taxa on a regular basis, despite the existence of clear rationales and even mandated authorizations to do so. Notably, the costs of monitoring jellyfish during regular fisheries research cruises would be a small increase over the cost of running a large fishery survey and a small fraction of the costs caused by impacts from these taxa. As ecosystems experience increasing pressures from climate change and fisheries, we recommend considering routine monitoring before some future jellyfish‐associated crisis arises.